Prevalence of smartphone addiction in an urban area of Kanchipuram district, Tamil Nadu: a cross sectional study - K., Renuka; S., Gopalakrishnan; R., Umadevi (International Journal Of Community Medicine And Public Health, 2019)
Background: The use of mobile phones especially smart phones have become an integral part of everyone’s life leading to addiction. Most of the studies conducted earlier were focused on youngsters. Hence this study was conducted to find out the prevalence of smart phone addiction in the study area. Methods: Community based cross sectional study carried out in Anakaputhur, Tamil Nadu from November 2018 to January 2019. Sample size of 400 was calculated using the formula 4PQ/L2. The respondents were selected by systematic random sampling. Subjects 18 years and above who are using mobile phones were included in the study. Data was analyzed using SPSS 16 version and presented using descriptive and analytical statistics. Results: Out of 405 participants 191 participants were non smart phone users and 214 were smart phone users. Overall prevalence of smart phone addiction was 27.6%. Male respondents were more addicted than the female (OR-1.94, 95%CI: 1.12-3.77, p=0.01). There was a statistically significant association between subjects <45 years of age and smart phone addiction (OR-2.33, 95% CI: 1.31-4.13, p=0.003) compared to older age group. Likewise respondents who were class III (modified BG Prasad Scale) and above were more addicted compared to subjects below class III (OR-2.29, 95% CI: 1.32-3.98, p=0.002). Conclusions: The prevalence of smart phone addiction is high that has to be addressed seriously. This can be tackled by better life style modification, awareness creation and attitudinal changes.